Rancang Bangun Aplikasi Persediaan Tristok dengan AppSheet di Apotek Trigadista Medica - Andi Nur Annisa Salsabila; Andi Ruslan; Syamsu Alam (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2026)
This research aims to construct an inventory management information system based on the no-code platform AppSheet, named Tristok, to automate medication stock recording procedures at Trigadista Medica Pharmacy. The urgency is driven by the pharmacy's dependence on manual systems that trigger data discrepancies and human error risks. The methodology employed is Research and Development (R&D) using the Waterfall development model, encompassing analysis, design, implementation, testing, and maintenance phases. System evaluation was conducted through field trials, expert judgment, and analysis using the Technology Acceptance Model (TAM) and Cost Benefit Analysis (CBA). The empirical findings indicate that the Tristok application successfully optimized transaction recording efficiency by 37% (from 127 seconds to 80 seconds) and eliminated inventory variances in real-time. The CBA results yielded a Benefit Cost Ratio (BCR) of 1.6, confirming that the system implementation is financially highly feasible. Holistically, Tristok has successfully transformed conventional manual workflows into an accountable and transparent data-driven management ecosystem.